Effects of Antimicrobial Peptide Microcin C7 on Growth Performance, Immune and Intestinal Barrier Functions, and Cecal Microbiota of Broilers - Dai, Ziqi; Shang, Lijun; Wang, Fengming; Zeng, Xiangfang; Yu, Haitao; Liu, Lu; Zhou, Jianchuan; Qiao, Shiyan (Frontiers in Veterinary Science, 2022)
Microcin C7 is an antimicrobial peptide produced by Escherichia coli, composed of a heptapeptide with a modified adenosine monophosphate. This study was performed to evaluate the effects of Microcin C7 as a potential substrate to traditional antibiotics on growth performance, immune functions, intestinal barrier, and cecal microbiota of broilers. In the current study, 300 healthy Arbor Acres broiler chicks were randomly assigned to one of five treatments including a corn–soybean basal diet and basal diet supplemented with antibiotic or 2, 4, and 6 mg/kg Microcin C7. Results showed that Microcin C7 significantly decreased the F/G ratio of broilers; significantly increased the levels of serum cytokine IL-10, immunoglobulins IgG and IgM, and ileal sIgA secretion; significantly decreased the level of serum cytokine TNF-α. Microcin C7 significantly increased villus height and V/C ratio and significantly decreased crypt depth in small intestine of broilers. Microcin C7 significantly increased gene expression of tight junction protein Occludin and ZO-1 and significantly decreased gene expression of pro-inflammatory and chemokine TNF-α, IL-8, IFN-γ, Toll-like receptors TLR2 and TLR4, and downstream molecular MyD88 in the jejunum of broilers. Microcin C7 significantly increased the number of Lactobacillus and decreased the number of total bacteria and Escherichia coli in the cecum of broilers. Microcin C7 also significantly increased short-chain fatty acid (SCFA) and lactic acid levels in the ileum and cecum of broilers. In conclusion, diet supplemented with Microcin C7 significantly improved growth performance, strengthened immune functions, enhanced intestinal barrier, and regulated cecal microbiota of broilers. Therefore, the antimicrobial peptide Microcin C7 may have the potential to be an ideal alternative to antibiotic.